1992
DOI: 10.1182/blood.v79.3.826.bloodjournal793826
|View full text |Cite
|
Sign up to set email alerts
|

Solvent/detergent-treated plasma: a virus-inactivated substitute for fresh frozen plasma

Abstract: Fresh frozen plasma (FFP) is prepared in blood banks world-wide as a by- product of red blood cell concentrate preparation. Appropriate clinical use is for coagulation factor disorders where appropriate concentrates are unavailable and when multiple coagulation factor deficits occur such as in surgery. Viral safety depends on donor selection and screening; thus, there continues to be a small but defined risk of viral transmission comparable with that exhibited by whole blood. We have prepared a virus sterilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 0 publications
6
129
0
2
Order By: Relevance
“…In agreement with previous reports [3–5,8], the current study demonstrated no viral transmission; however, passive immunization was evident for both anti‐HAV IgG and parvovirus B19 IgG.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports [3–5,8], the current study demonstrated no viral transmission; however, passive immunization was evident for both anti‐HAV IgG and parvovirus B19 IgG.…”
Section: Discussionsupporting
confidence: 93%
“…It has been developed by Octapharma (Octapharma AG, Lachen, Switzerland) and is obtained by the proportional pooling of A, B and AB plasma in order to neutralize anti‐A and anti‐B immunoglobulins by A and B antigens (substances), and possible anti‐idiotypic antibodies, in plasma [2]. Virus inactivation is achieved by solvent/detergent (SD) treatment [3]. SD treatment is a well‐documented method used for virus inactivation and an extremely effective way to eliminate enveloped viruses from plasma and plasma products [4], while non‐enveloped viruses can be inhibited by immune antibodies in the plasma pool [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, these technologies aim at altering pathogen nucleic acids and the conditions have been developed for preserving PLT integrity, 41 therefore limiting the release of the GF from the α‐granules. The reasons why we selected the S/D treatment are directly linked to the fact that it is a well‐established procedure to destroy lipid‐enveloped viruses that 1) preserves the functional activity of most proteins, 38,40,42 2) induces PLT lysis and massive release of GF, 31 and 3) can be readily applied to pooled PLT concentrates for small‐, medium‐, or large‐scale production as it has been for plasma products 43 . Removal of the S/D agents can be achieved by oil extraction and hydrophobic interaction chromatography, a mild process already used in the plasma industry 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The reasons why we selected the S/D treatment are directly linked to the fact that it is a well‐established procedure to destroy lipid‐enveloped viruses that 1) preserves the functional activity of most proteins, 38,40,42 2) induces PLT lysis and massive release of GF, 31 and 3) can be readily applied to pooled PLT concentrates for small‐, medium‐, or large‐scale production as it has been for plasma products 43 . Removal of the S/D agents can be achieved by oil extraction and hydrophobic interaction chromatography, a mild process already used in the plasma industry 43 . The process includes centrifugation and a 0.2‐µm filtration step that remove blood cell membrane fragments, therefore reducing risks of alloimmunization in treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…The process provides for complete penetration of the inner matrices of tissue, removal of any contaminants as well as blood, bone marrow, and other unwanted endogenous materials through an extensive serial dilution process [26, 27]. As part of the BioCleanse ® process, two detergents, which have been proven to be inactivators of enveloped viruses, are used in combination [28, 29]. In accordance with the standardized BioCleanse ® protocol, bovine bone samples were submerged in a closed chamber and exposed to the previously mentioned cleansing solutions at varying pressures and alternated with vacuum cycles.…”
Section: Methodsmentioning
confidence: 99%